Genetic transfer from several apomictic tetraploid paspalum species to an elite group of sexual plants - Novo, Patricia Elda (2020)
Fil: Novo, Patricia Elda. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.